Voclosporin: a novel calcineurin inhibitor with no impact on mycophenolic acid levels in patients with SLE. Issue 5 (2nd February 2021) - van Gelder, Teun; Huizinga, Robert B; Lisk, Laura; Solomons, Neil
Abstract: Background: An open-label phase 1 study was conducted to evaluate the effect of voclosporin following dosing with mycophenolate mofetil (MMF) on blood levels of mycophenolic acid (MPA, the active moiety of MMF) and MPA glucuronide (MPAG, the pharmacologically inactive metabolite of MMF) in subjects with systemic lupus erythematosus (SLE) and to assess the safety and tolerability of the combination. Methods: MMF was orally administered at a dose of 1 g twice a day for at least 28 days prior to the study and continued at the same dose throughout the study. Voclosporin was orally administered at a dose of 23.7 mg twice a day for 7 consecutive days (Days 1–7), starting on the evening of Day 1 and ending with the morning dose on Day 7. Dense pharmacokinetic blood samples were collected pre-dose in the morning and from 0.25 to 12 h after the morning doses. Analyses were derived by non-compartmental methods. Results: In 24 patients, MPA exposure [maximum serum concentration ( C max ) and area under the concentration curve from time 0 to 12 h (AUC0–12 )] was similar in the presence and absence of voclosporin, with treatment ratios of 0.94 and 1.09, respectively [ C max 16.5 μg/mL (Day 1) versus 15.8 (Day 7), AUC0–12 39.1 μg/h/mL (Day 1) versus 40.8 (Day 7)]. MPAG exposure showed a small increase in the presence of voclosporin (12% for C max and 27% for AUC0–12 ). Combination therapy was well tolerated. Conclusions: There is no clinically meaningful interaction between voclosporin and MMF. As changes in exposure to MPA may affect efficacy and safety, these data confirm that voclosporin and MMF can be administered concomitantly without the need for dose adjustment.